Experimental Determination of the Elastic and Viscous Behavior of Polycarbonate Melts at Different Temperatures and Their Relationship to the Steady State Viscosity via the Cox-Merz Rule - K. Muallah, Shatha (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Rheological instrument is one of the basic analytical measurements for diagnosing the properties of polymers fluids to be used in any industry. In this research polycarbonate was chosen because of its importance in many areas and possesses several distinct properties.Two kinds of rheometers devices were used at different range of temperatures from 220 ˚C-300 ˚C to characterize the rheological technique of melted polycarbonate (Makrolon 2805) by a combination of different investigating techniques. We compared the results of the linear (oscillatory) method with the non-linear (steady-state) method; the former method provided the storage and the loss modulus of melted polycarbonate, and presented the Cox-Merz model as well. One of the major problems in measuring the viscosity of polycarbonate at high shear rates, especially at the extremes of temperatures, was that during the use of the capillary rheometer, long molecule chains led to high viscosity.